Genome‐wide association study reveals putative regulators of bioenergy traits in Populus deltoides. Issue 2 (6th September 2016) - Fahrenkrog, Annette M.; Neves, Leandro G.; Resende, Márcio F. R.; Vazquez, Ana I.; de los Campos, Gustavo; Dervinis, Christopher; Sykes, Robert; Davis, Mark; Davenport, Ruth; Barbazuk, William B.; Kirst, Matias
Summary: Genome‐wide association studies (GWAS) have been used extensively to dissect the genetic regulation of complex traits in plants. These studies have focused largely on the analysis of common genetic variants despite the abundance of rare polymorphisms in several species, and their potential role in trait variation. Here, we conducted the first GWAS in Populus deltoides, a genetically diverse keystone forest species in North America and an important short rotation woody crop for the bioenergy industry. We searched for associations between eight growth and wood composition traits, and common and low‐frequency single‐nucleotide polymorphisms detected by targeted resequencing of 18 153 genes in a population of 391 unrelated individuals. To increase power to detect associations with low‐frequency variants, multiple‐marker association tests were used in combination with single‐marker association tests. Significant associations were discovered for all phenotypes and are indicative that low‐frequency polymorphisms contribute to phenotypic variance of several bioenergy traits. Our results suggest that both common and low‐frequency variants need to be considered for a comprehensive understanding of the genetic regulation of complex traits, particularly in species that carry large numbers of rare polymorphisms. These polymorphisms may be critical for the development of specialized plant feedstocks for bioenergy.